PERUBAHAN PROGRESIF DALAM PEMBELAJARAN PAI BERBASIS TEKNOLOGI INFORMASI DAN KOMUNIKASI - Arief Rifkiawan Hamzah (AT-TAJDID, 2018)
This article explains about PAI learning by utilizing information and communication technology (ICT). PAI learning in Indonesia needs to be integrated with ICT, because it can open various avenues for teachers to more easily convey material and learners can also more easily understand. Illustrations which in the past were only made by teachers by drawing manually and made with paper, have now changed with the presence of a variety of good hardware and software. Learning by utilizing ICT can change the paradigm and teaching and learning process, both from the teacher and students.The progressive changes can be felt together, provided that all education providers support by providing various types of facilities